Layered Double Hydroxides: A Novel Promising 2D Nanomaterial for Bone Diseases Treatment - Yixin Bian; Xuejie Cai; Zehui Lv; Yiming Xu; Han Wang; Chaoliang Tan; Ruizheng Liang; Xisheng Weng (Advanced Science, 2023)
Abstract Bone diseases including bone defects, bone infections, osteoarthritis, and bone tumors seriously affect life quality of the patient and bring serious economic burdens to social health management, for which the current clinical treatments bear dissatisfactory therapeutic effects. Biomaterial‐based strategies have been widely applied in the treatment of orthopedic diseases but are still plagued by deficient bioreactivity. With the development of nanotechnology, layered double hydroxides (LDHs) with adjustable metal ion composition and alterable interlayer structure possessing charming physicochemical characteristics, versatile bioactive properties, and excellent drug loading and delivery capabilities arise widespread attention and have achieved considerable achievements for bone disease treatment in the last decade. However, to the authors' best knowledge, no review has comprehensively summarized the advances of LDHs in treating bone disease so far. Herein, the advantages of LDHs for orthopedic disorders treatment are outlined and the corresponding state‐of‐the‐art achievements are summarized for the first time. The potential of LDHs‐based nanocomposites for extended therapeutics for bone diseases is highlighted and perspectives for LDHs‐based scaffold design are proposed for facilitated clinical translation.